(untitled) (CIPEEX, 2022)
HEMATOLOGICAL ASPECTS IN PATIENTS WITH THECOVID-19: A SYSTEMATIC REVIEWDEISE A. A. PIRES OLIVEIRA 1BEATRIZ SIQUEIRA SILVA 2PROFESSOR OF THE MEDICAL COURSE AT THE EVANGELICAL UNIVERSITY OF ANÁPOLIS - UNIEVANGLICA¹STUDENT OF THE MEDICAL COURSE AT THE EVANGELICAL UNIVERSITY OF ANÁPOLIS - UNIEVANGLICA²INTRODUCTIONTHE COVID-19 PANDEMIC HAS CAUSED A HEALTH CRISIS ON THE PLANET, WITHTHIS IS CAUSED BY A HIGHLY CONTAGIOUS VIRAL DISEASE, FIRST IDENTIFIEDONCE IN CHINA IN 2019, WHICH LEFT, AND STILL HAS, MANY DEATHS AROUND THE WORLD.WORLD, AND THE VIRUS THAT CAUSES THIS DISEASE, CALLED THE NEW CORONAVIRUS, IS AVARIATION OF THE SARS-COV-2 VIRUS (SOUZA ET AL., 2021).THE DISEASE CAUSED BY THE CORONAVIRUS, COVID-19, MANIFESTS ITSELF,TYPICALLY AS A RESPIRATORY TRACT INFECTION, WHICH MAY AFFECT SEVERAL ORGANSAND BODY SYSTEMS, INCLUDING THE HEMATOPOIETIC. THE DISEASE COURSE OF COVID-19CAN OCCUR WITH THE INSTALLATION OF SERIOUS INFECTIONS, WHICH WILL CAUSE A RESPONSEINFLAMMATION GREATER THAN NORMAL, WHICH MAY RESULT IN HEMATOLOGICAL CHANGES,AMONG THEM THE HYPERCOAGULABILITY THAT CAN PRESENT ITSELF AS PART OF THE COAGULATIONDISSEMINATED INTRAVASCULAR DISEASE (DIC), THROMBOEMBOLIC EVENTS AND THEMACROPHAGE ACTIVATION (FLEURY, 2020); (NICOLAU, 2020).IN THE EVALUATION OF THE GENERAL CONDITION OF A PATIENT AFFECTED BY THE COVID 19 VIRUS, THE RESULTS OF HEMATOLOGICAL EXAMS ARE ESSENTIAL IN THE KNOWLEDGE OF THEIMMUNOLOGICAL LEVELS OF THE PATIENT, WHICH DIRECTLY INTERFERES IN THE COURSE OF THE DISEASE.ITS RESULTS CAN BE USED AS A PROGNOSTIC MARKER AND ALSO FORTREATMENT AND FOLLOW-UP OF THE PATIENT’S EVOLUTION (GIL ET AL., 2020). SO,IT IS CLEAR THAT THE HEMATOLOGICAL FINDINGS ARE IMPORTANT FROM THE BEGINNING OF THE DISEASE,ASSESSING WHETHER THE TREATMENT IS BEING EFFECTIVE, DESPITE THE FACT THAT THERE IS STILL NO TREATMENTSPECIFIC, AS WELL AS IF THERE IS A NEED FOR EMERGENCY MEASURES. THEREFORE, DISCUSSCIPEEX - INTERNATIONAL CONGRESS OF RESEARCH, TEACHING AND EXTENSIONV.3 (2022) - ISSN: 2596-1578TWOASPECTS INVOLVING HEMATOLOGY IN COVID-19 IS EXTREMELY RELEVANT ANDIMPORTANCE (GIL ET AL., 2020).IN GENERAL, THE MOST COMMON HEMATOLOGICAL CHANGES FOUNDIN COVID-19 ARE LYMPHOPENIA, LEUKOPENIA, NEUTROPENIA, LEUKOCYTOSIS, EOSINOPENIA,DECREASED HEMOGLOBIN, THROMBOCYTOPENIA, PLATELET AGGREGATION, INCREASED D-DIMER,PROTHROMBIN TIME (PT) AND ACTIVATED PARTIAL THROMBOPLASTIN TIME (APTT), BETWEENOTHERS, THESE ALTERATIONS BEING IMPORTANT PREDICTORS OF THE DISEASE AND ESSENTIAL IN THEMONITORING OF CORONAVIRUS CASES (PEREIRA ET AL., 2021).THUS, DESPITE THE DIFFICULTIES STILL ENCOUNTERED IN CONDUCTING THE CASES ANDTREATMENT, THE RESULTS OF HEMATOLOGICAL TESTS ARE ESSENTIAL IN THE EVALUATION OFPROGNOSIS AND TREATMENT, THESE TESTS HAVING A DIRECT RELATIONSHIP WITH THE EFFECT THAT THE VIRUSIT IS ABLE TO PROVOKE IN CELLS AND THROUGHOUT THE BODY (RUPPENTHAL ET AL., 2021). MATERIALS AND METHODSFOR THE DEVELOPMENT OF THE PRESENT WORK, A SEARCH WAS CARRIED OUT FOR THESTUDIES THAT CONTEMPLATE THE THEME, WHICH WERE RESEARCHED AND SELECTED FORTHIS REVIEW. STUDIES THAT ANALYZE THE PROFILE OF INVOLVEMENT WERE INCLUDED.HEMATOLOGY OF PATIENTS WITH THE COVID-19 VIRUS, AS WELL AS THEOVERVIEW OF THE COVID-19 PANDEMIC. THE ARTICLES WERE SELECTED IN THE DIFFERENTAVAILABLE DATABASES SUCH AS SCIELO, PUBMED, GOOGLE SCHOLAR, DYNAMED ANDTHEN THEY WERE ANALYZED SO THAT ALL MET THE INCLUSION CRITERIANEEDED. ALSO, THE PROJECT WAS SUBMITTED TO THE REGISTRATION OF THE PROSPERO PLATFORM, AREGISTRY BASE OF SYSTEMATIC REVIEW PROTOCOLS, BEING APPROVED, WITH NUMBERREGISTRATION CRD42022312844.KEYWORDS: COVID-19; HEMATOLOGY; PANDEMICRESULTSIT IS KNOWN THAT ALTHOUGH THE MAIN SITE OF INFECTION OF THE CORONAVIRUS IS THERESPIRATORY SYSTEM, THE DISEASE MANIFESTS SYSTEMIC CHARACTERISTICS, AMONG THEM,IMPORTANT HEMATOLOGICAL CHANGES. THE EFFECT THAT THE VIRUS IS ABLE TO HAVE ON THEHEMATOLOGICAL SYSTEM IS AN IMPORTANT GUIDE TO THE SEVERITY OF THE DISEASE. BETWEEN THEPOSSIBLE ALTERATIONS, THE MAIN AND MOST FREQUENT ARE LYMPHOPENIA, CONCOMITANT WITHEXACERBATED PRODUCTION OF PRO-INFLAMMATORY CYTOKINES, DECREASED HEMOGLOBIN,THROMBOCYTOPENIA, LYMPHOPENIA, INCREASED D-DIMER, PT AND APTT, WHICHDEPENDING ON THE LEVEL OF CHANGE, ARE RELATED TO THE WORST OUTCOME OF THE INFECTION(RUPPENTHAL ET AL., 2021).AMONG THE HEMATOLOGICAL DISORDERS, THERE IS AN IMPORTANT ALTERATION OF THECOAGULATION CASCADE, WHICH WAS OBSERVED MAINLY IN PATIENTS WITHSEVERE DISEASE ONSET. (COELHO ET AL., 2021). AMONG THESE PARAMETERS,INCREASED PT WAS OBSERVED IN SEVERE PATIENTS, WHILE MILDER CASES DID NOTDEVELOPED CHANGES. IN THE CASE OF TTPA, ITS INCREASE WAS FOUND BOTH INMILD TO SEVERE CASES, AS WELL AS THE D-DIMER, WITH WORSENING OBSERVED IN THE LATTER.AS THE PATIENT PROGRESSED TO MORE SEVERE DISEASE STATES. STILL, THEANALYSIS OF INFLAMMATORY PARAMETERS SHOWED THAT PATIENTS WITH WORSE OUTCOMEHAD INCREASED CRP (SILVA ET AL., 2022).OF THE ALTERATIONS FOUND, THERE SEEMS TO BE AN ORDER OF INVOLVEMENT,NEUTROPENIA BEING ONE OF THE FIRST ALTERATIONS FOUND, TOGETHER WITH THELYMPHOPENIA, BOTH RELATED TO INCREASED INFLAMMATION AND CYTOKINE PRODUCTIONINFLAMMATORY. FURTHERMORE, BOTH ALTERATIONS ARE RELATED TO THE SEVERITY OF THE DISEASE.(REIS, FILHO, BORGES, 2022). HEMATOLOGICAL CHANGES ARE A CONSEQUENCE OF BOTHDIRECT ACTION OF THE VIRUS ON CELLS, AS WELL AS INDIRECT (RUPPENTHAL ET AL., 2021).STILL ON THE INFLAMMATORY ANALYSIS, HEMATOLOGICAL ANALYSIS IS ESSENTIAL IN THEASSESSMENT OF CHANGES THAT LEAD TO THE DEVELOPMENT OF SEPSIS (FLEURY 2020).DEREGULATED CLOTTING MECHANISMS WERE RESPONSIBLE FOR CAUSINGTHROMBOEMBOLIC COMPLICATIONS IN PATIENTS, WHICH IS A COMPLICATIONRELATIVELY COMMON OBSERVED IN PATIENTS WITH COVID-19 (COELHO ET AL.,2021). IN ADDITION TO THE CHANGE IN PLATELET COUNT, CHANGES WERE OBSERVED INITS MORPHOLOGY, MAINLY, GIANT PLATELETS, MORE COMMONLY IN PATIENTSIN MORE SEVERE STAGES OF THE DISEASE (PEREIRA ET AL., 2021). STILL, THE CHANGESTHROMBOCYTOPENIC THROMBOSIS, BEING ALSO RELATED TO LONGERHOSPITALIZATION OF PATIENTS (FLEURY 2020).IN ADDITION TO THESE CHANGES, PATIENTS WHO DIED, FOR THE MOST PART,STUDIED WITH EOSINOPHILIA, WHICH IS A FINDING THAT HELPS TO IDENTIFY THE EVOLUTIONOF DISEASE SEVERITY. LIKEWISE, ALTHOUGH IT WAS NOT A COMMON FINDINGIN PATIENTS, THOSE WITH HEMOGLOBIN VALUES €‹€‹LOWER THAN TEN, WITHDEVELOPMENT OF ANEMIA, WERE MORE LIKELY TO DEVELOPFOR A SEVERE CONDITION (PEREIRA ET AL., 2021). SEVERE GROUPS ALSO SHOWEDINCREASE IN RDW DUE TO BONE MARROW SUPPRESSION CAUSED BY THE VIRUS,ALTERING THE MORPHOLOGY OF HEMATOLOGICAL LINEAGES. FURTHERMORE, THE HEMOGLOBININFECTED PATIENTS, DEVELOPED A CHANGE IN THE HEME GROUP, WHICH CONTRIBUTES TOTHE WORSENING OF RESPIRATORY CONDITIONS (PEREIRA ET AL., 2021).IN ADDITION TO THE CHANGES OBSERVED IN GENERAL, IT SHOULD BE NOTED THATTHERE IS A WORSE OUTCOME OF THE DISEASE AND THE EVOLUTION OF THE HEMATOLOGICAL INVOLVEMENT INCERTAIN POPULATIONS, SUCH AS OLDER PATIENTS, WITH COMORBIDUNDERLYING CONDITIONS AND, STILL, A GREATER PREDOMINANCE OF SEVERITY IN PATIENTS OF THE SEXMASCULINE. AMONG THE MOST COMMON COMORBIDITIES, HYPERTENSION WAS FOUND.SYSTEMIC ARTERIAL DISEASE, TYPE 2 DIABETES MELLITUS AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE (REIS,SON, BORGES, 2022). CONCLUSIONLABORATORY HEMATOLOGICAL PROFILE DURING COVID-19 VIRUS INFECTIONIS IMPORTANT FOR THE PURPOSES OF PROGNOSIS AND TREATMENT OF THE DISEASE. IN THE REVIEWSYSTEMATIC ANALYSIS OF HEMATOLOGICAL CHANGES, THE MOST EXPECTED IN PATIENTS WITHCOVID-19 INFECTION ARE LYMPHOPENIA, NEUTROPHILIA, THROMBOCYTOPENIA, AND CHANGES ININFECTIOUS PATTERN, SUCH AS INCREASED CRP AND D-DIMER. (REIS, SON, BORGES,2022). IN GENERAL, THE UNDERSTANDING OF THE REPERCUSSION THAT THE DISEASE OF COVID 19 IS CAPABLE OF CAUSING IN THE HEMATOLOGICAL ASPECTS OF THE PATIENT, CORROBORATES THEPROGNOSIS, TREATMENT AND EVEN PROPHYLAXIS OF CERTAIN CONDITIONS, BEINGMONITORING IS ESSENTIAL FOR A BETTER OUTCOME OF THE CASES (COELHO ET AL.,2021).BIBLIOGRAPHIC REFERENCES 1. COELHO, F.A.R. ET AL. ALTERAES HEMATOLÓGICAS EM PACIENTES ACOMETIDOS PELA COVID-19. RESEARCH, SOCIETY AND DEVELOPMENT, V.10, N.17, P.1-10, 2021. 2. FLEURY, M.K. A COVID-19 E O LABORATÓRIO DE HEMATOLOGIA: UMA REVISÃO DA LITERATURA RECENTE. REVISTA BRASILEIRA DE ANLISES CLNICAS, V.25, N.2, P.131-137, 2020. 3. GIL, E.M. ET AL. HEMATOLOGA EN POCA DEL COVID-19. RECIMAUC, V.4, N.3, P. 288-297, 2020. 4. NICOLAU, D.I. PROTOCOLO COVID-19: MANEJO DAS COMPLICAES HEMATOLÓGICAS. MARIA DOS REMDIOS BRANCOS, P.1-17, 2020.5. PEREIRA, A.F. ET AL. ALTERAES HEMATOLÓGICAS E HEMOSTASIA NA COVID-19: UMA REVISÃO DE LITERATURA. RESEARCH, SOCIETY AND DEVELOPMENT, V.10, N.11, P.1-17, 2021.6. ROJAS, P.; SARMIENTO, M. PERSPECTIVA HEMATOLÓGICA EM EL TRATAMENTO DE PACIENTES CON COVID-19: ROL DE LOS TRATAMIENTOS ANTIINFLAMATORIOS. REVISTA MDICA DE CHILE, V.148, P.1640-1646, 2020. 7. REIS, K.N.; FILHO. J.M.O.; BORGES. F.S. HEALTH RESIDENCIES JOURNAL, V.3, N.5, P.1-27, 2022. 8. RUPPENTHAL, G. ET AL. ALTERAES HEMATOLÓGICAS EM PACIENTES COM COVID-19: UMA REVISÃO INTEGRATIVA DA LITERATURA. REVISTA SAÚDE, V.47, N.1, 2021.9. SILVA, G.F.R.D. ET AL. COMPARAO DOS PERFIS BIOQUMICOS E HEMATOLÓGICOS DE PACIENTES COM COVID-19 EM SEUS DIFERENTES DESFECHOS: ALTA HOSPITALAR E ÓBITO. RESEARCH, SOCIETY AND DEVELOPMENT, V. 11, N2, P. 1-18, 2022. 10. SOUZA, A.S.R. ET AL. GENERAL ASPECTS OS THE COVID-19 PANDEMIC. REVISTA BRASILEIRA DE SAÚDE MATERNA E INFANTIL, V.21, P.29-46, 2021. THANKSI THANK THE RESEARCH, TEACHING AND EXTENSION CONGRESS AND THESCIENTIFIC INITIATION SCHOLARSHIPS FOR THE OPPORTUNITY AND COLLABORATION WITH THE PRESENTWORK, I THANK THE GUIDING TEACHER AND THE ENTIRE EVALUATION BOARD.